2006
DOI: 10.1002/jbm.a.30603
|View full text |Cite
|
Sign up to set email alerts
|

Alginate hydrogel and matrigel as potential cell carriers for neurotransplantation

Abstract: Development of biosynthetic conduits carrying extracellular matrix molecules and cell lines expressing neurotrophic growth factors represents a novel and promising strategy for spinal cord and peripheral nerve repair. In the present in vitro study, the compatibility and growth-promoting effects of (i) alginate hydrogel, (ii) alginate hydrogel complemented with fibronectin, and (iii) matrigel were compared between olfactory ensheathing cells (OECs), Schwann cells (SCs), and bone marrow stromal cells (BMSCs). Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
122
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(129 citation statements)
references
References 61 publications
3
122
1
3
Order By: Relevance
“…Growth factors such as TGF-β, basic fibroblast growth factor, insulin-like growth factor-1 and tissue plasminogen activator are also present (Novikova et al, 2003;Kleinman and Martin, 2005). Matrigel has previously been used in neuronal culture and has been shown to stimulate neurite outgrowth in vitro (Tisay and Key, 1999;Novikova et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Growth factors such as TGF-β, basic fibroblast growth factor, insulin-like growth factor-1 and tissue plasminogen activator are also present (Novikova et al, 2003;Kleinman and Martin, 2005). Matrigel has previously been used in neuronal culture and has been shown to stimulate neurite outgrowth in vitro (Tisay and Key, 1999;Novikova et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As the cross-linking multivalent cations gradually diffuse out from the gel, it slowly degrades and is excreted in urine. Alginate gels are frequently used as matrices for encapsulation of living cells and for the release of proteins (Novikova et al, 2006;Tobias et al, 2001Tobias et al, , 2005. In regeneration studies, alginate gels are often applied as cell carrier substances.…”
Section: Alginatementioning
confidence: 99%
“…Alginate has been described to enhance neuronal sprouting and to decrease inhibitory cues after CNS trauma (Kataoka et al, 2004;Prang et al, 2006), but other studies have also reported a lack of axon growth stimulation mediated by alginate scaffolds (Estrada et al, 2014;Novikova et al, 2006). In vitro studies have even demonstrated that this biomaterial can inhibit the growth of dorsal root ganglion neurons and cause alteration of the phenotype of various different cell types (Novikova et al, 2006). This gel is, however, a quite suitable matrix for the encapsulation of cells with or even without further modification of the material.…”
Section: Alginatementioning
confidence: 99%
See 2 more Smart Citations